2016
DOI: 10.18488/journal.1005/2016.6.11/1005.11.221.228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of several cultivars`: Mulch and fertilizer applications on plant growth and development criteria and plant`s nutrition elements uptake in organic strawberry plantation in Nevşehir city

Abstract: This study was conducted to investigate the effect of different mulch types' (black plastic, textile and sawdust) and fertilizer applications (Ekoflora, Mog, Bio-one, Ferbanat L and Natural Bioplasma) effect in strawberry (Fragaria vesca L.) cultivars ('Monterey', 'Albion', 'Aromas', 'Camarosa' and 'Sweet Charlie'). The effects of applications on plant nutrient concentrations (N, P, K, Ca, Mg and Fe) and plant growth and development criteria (plant height, steam diameter, number of leaf and root height) were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Ornelas-Paz [70] reported that the highest TSS value was 9.00% from RS6. Şener and Türemiş [58] reported that the highest TSS value of 9.05% was obtained from Albion. The TSS values obtained from the above studies are compatible with the TSS values obtained from our study.…”
Section: Fruit Parametersmentioning
confidence: 96%
See 3 more Smart Citations
“…Ornelas-Paz [70] reported that the highest TSS value was 9.00% from RS6. Şener and Türemiş [58] reported that the highest TSS value of 9.05% was obtained from Albion. The TSS values obtained from the above studies are compatible with the TSS values obtained from our study.…”
Section: Fruit Parametersmentioning
confidence: 96%
“…Ornelas-Paz [70], in his study examining the ripening stages of the organically grown Albion strawberry variety, reported that the highest TSS value was 3.80% from the RS6. Şener and Türemiş [58] reported that the highest pH value was 3.83% from Camaroza and 3.65% from Alnion. Karaca and Pırlak [65] reported that the highest pH value was obtained from 3.83% Albion.…”
Section: Fruit Parametersmentioning
confidence: 96%
See 2 more Smart Citations
“…One of them is by doing fertilization. Fertilization is the most important factor in growth and development until the result of production [23]. He also states that fertilizing using organic fertilizer is as important as fertilizing by using inorganic fertilizer for plant growth process.…”
Section: Dry Weight Of Plantmentioning
confidence: 99%